2015
DOI: 10.3354/dao02854
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of three protozoan symbionts in blue crab (Callinectes sapidus) populations across Louisiana, USA

Abstract: Louisiana has one of the largest blue crab (Callinectes sapidus) fisheries in the USA, but little is known about blue crab diseases, parasites, and symbionts in this area. In 2013-2014, large juvenile and adult blue crabs were collected at 4 diverse sites to determine the prevalence of the protozoan symbionts associated with black gill disease (Lagenophrys callinectes), buckshot crabs (Urosporidium crescens), and bitter crab disease (Hematodinium perezi). A high aggregate prevalence of L. callinectes (93.2%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…The overall prevalence of H. perezi detected in blue crab post-larvae (11.2%) was just below the range of 12−15% reported by Hamilton et al (2011) for unidentified crab larvae from the Clyde Sea. The absence of crabs with detectable H. perezi in marshes as documented in this study and others (Messick & Shields 2000, Pagenkopp Lohan et al 2013, Rogers et al 2015a could be explained by a low survival rate for megalopae impacted by H. perezi, a lack of transmission in low salinity waters, elimination of the parasite in low salinity habitats or a combination of these mechanisms. More work is needed to assess the importance of H. perezi in early life stages of the blue crab.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The overall prevalence of H. perezi detected in blue crab post-larvae (11.2%) was just below the range of 12−15% reported by Hamilton et al (2011) for unidentified crab larvae from the Clyde Sea. The absence of crabs with detectable H. perezi in marshes as documented in this study and others (Messick & Shields 2000, Pagenkopp Lohan et al 2013, Rogers et al 2015a could be explained by a low survival rate for megalopae impacted by H. perezi, a lack of transmission in low salinity waters, elimination of the parasite in low salinity habitats or a combination of these mechanisms. More work is needed to assess the importance of H. perezi in early life stages of the blue crab.…”
Section: Discussionsupporting
confidence: 67%
“…Infection has been observed less frequently in waters with salinities below 11 ppt (Messick & Shields 2000), while severe outbreaks are often associated with high salinities following droughts (Lee & Frischer 2004, Parmenter et al 2013, Gandy et al 2015. In all of the previous surveys for H. perezi that included blue crabs from Louisiana, USA, none detected the pathogen in Louisiana (Messick & Shields 2000, Pagenkopp Lohan et al 2013, Rogers et al 2015a although infected crabs have been reported from the Gulf coasts of Texas, Florida and Mississippi, USA (Newman & Johnson 1975, Messick & Shields 2000, Shields & Overstreet 2007, Gandy et al 2015. The relatively low salinities of Louisiana's inshore waters, combined with limited sampling from higher salinity offshore habitats could explain the apparent absence of H. perezi in Louisiana.…”
Section: Introductionmentioning
confidence: 99%